PIVKA-II as a Potential New Biomarker for Hepatocellular Carcinoma - A Pilot Study - Svobodova, Sarka; Karlikova, Marie; Topolcan, Ondrej; Pecen, Ladislav; Pestova, Martina; Kott, Otto; Treska, Vladislav; Slouka, David; Kucera, Radek (In vivo (Athens, Greece), 2018)
AIM: The aim of this study was to evaluate the clinical contribution of protein induced by vitamin K absence (PIVKA-II) for hepatocellular carcinoma (HCC) diagnostics and compare it with alpha-foetoprotein (AFP), a routinely used tumour marker. MATERIALS AND METHODS: A total of 332 participants were enrolled in this study: 64 with HCC, 48 with liver metastases of colorectal cancer origin, 42 with liver cirrhosis and 178 healthy individuals. Serum levels of PIVKA-II were measured using the chemiluminescent assay of the Architect 1000i System (Abbott, USA) and AFP levels using the chemiluminescent assay by DxI 800 (Beckman Coulter, USA). RESULTS: PIVKA-II achieved better clinical sensitivity than AFP and the difference in this sensitivity was statistically significant. PIVKA-II achieved the best sensitivity (96.9%) in distinguishing between the HCC and control groups with the proposed cut-off value of 60 mAU/ml. CONCLUSION: Our recommendation is for addition of PIVKA-II to the routine panel of HCC tumour markers.
Keywords: Liver Cirrhosis; Male; biologické markery; Biomarkers; pilotní projekty; biomarkers; AFP; Carcinoma, Hepatocellular; Adult; PIVKA-II; Diagnosis, Differential; Aged; dospělí; mužské pohlaví; senioři; predictive; hepatocellular carcinoma; protrombin; senioři nad 80 let; lidé; jaterní cirhóza; ženské pohlaví; nádory jater; Biomarkers, Tumor; Humans; diferenciální diagnóza; hepatocelulární karcinom; Aged, 80 and over; Prothrombin; Protein Precursors; Pilot Projects; Liver Neoplasms; Female; proteinové prekurzory; lidé středního věku; nádorové biomarkery; Middle Aged